Factors Associated with SARS-CoV-2 Antibody Titer After Sinovac Vaccination Among Health Care Workers - Theresia Santi; Baringin De Samakto; Lina Kamarga; Feronica Kusuma Hidayat; Ferry Hidayat (Interna Publishing, 2022)
Background: One of the methods to record immunogenicity after vaccination is to measure antibody titer. This study aimed to get the value of antibody titer post Sinovac vaccination and to analyze factors that associate with it. The trend of titer changes within 3 months period and the incidence of COVID-19 were also observed. Methods: A prospective cohort study was conducted in March until May 2021 involving 250 health care workers of Siloam Hospitals Lippo-Cikarang who have completed two doses of Sinovac vaccination. We collected 3 titer data from each participant to observe the trend of changes. The incidence of COVID-19 among post-vaccinated subjects was also calculated. Results: From total of 250 participants, 88 (35.2%) were males and 162 (64.8%) were females. Fourteen days after vaccination, 248 subjects (99.2%) had seroconversion. The median antibody titer amounted to 63.58 U/ml (0.4->250 U/ml). The titer was higher in age group 26-39 years (85.1 U/ml, p=0.003) and in women (78.7 U/ml, p=0.007). Within 3 months period, 162 from 200 participants (81%) who completed 3 titer tests, had antibody titer reduction (p=0.231). In observation, 94 from 245 (38.3%) participants tested positive COVID-19, with only 5 out of 94 (5.3%) participants being hospitalized. Conclusion: The highest median titer was achieved 14 days after Sinovac vaccination (63.58 U/ml). Younger age group and women are associated with higher value. The reduction trend in titer within 3 months is insignificant. Among post-vaccinated infection subjects, the hospitalization rate is low, which shows that Sinovac vaccination still has a protective effect.